Multiclass Document Classifier using BERT - Shruti A. Gadewar; Prof. P. H. Pawar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
With the rapid expansion of the internet, there has been an exponential surge in data volume, encompassing a myriad of documents laden with diverse types of information. This vast expanse includes structured and unstructured data, ranging from big data sets to formatted text and unformatted content. However, this abundance of unstructured data poses significant challenges in terms of effective management. Manual classification of this burgeoning data landscape is impractical, necessitating automated solutions. In this paper, we propose leveraging advanced machine learning techniques, particularly the BERT model, to classify documents based on contextual understanding, offering a more efficient and accurate approach to handling the data deluge.